Evidence-Based Practices and Implementation Science in Special Education. (January 2013) - Cook, Bryan G.; Odom, Samuel L.
Establishing a process for identifying evidence-based practices (EBPs) in special education has been a significant advance for the field because it has the potential for generating more effective educational programs and producing more positive outcomes for students with disabilities. However, the potential benefit of EBPs is bounded by the quality, reach, and maintenance of implementation. The cross-disciplinary field of implementation science has great relevance for translating the promise of EBPs into positive outcomes for children and youth with disabilities. This article examines the history, extent, and limitations of EBPs and describes the emergence and current state of implementation science as applied in special education. Subsequent articles in this special issue of Exceptional Children address a range of issues related to implementation science in special education: the research-to-practice gap, dissemination and diffusion, adherence and sustainability, scaling up, a model for state-level implementation, and fostering implementation through professional development.